Environmental pollutants and their impact on COVID‐19 spread: Current problem and future resolutions. Issue 1 (30th January 2023) - Patil, Pooja M.; Parthasarathy, Arun K.; Matkar, Abhijeet R.; Mahamuni‐Badiger, Pranjali; Dhanavade, Maruti J.
Abstract: COVID‐19 is the greatest crucial universal health issue of the century and the extreme challenge that came after the 2nd World War faced by humankind. In 2019, different strains of the coronavirus have emerged drastically, that as severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) which is the causative agent of corona disease. As far as human civilization history, there have been occurrences of severe diseases and outbreaks of various viruses. According to World Health Organization reports, throughout the world, the present outbreak of COVID‐19 has engulfed more than 200 countries affecting 241, 471, 559 individuals and more than 4, 914, 092 people lost their lives. SARS‐CoV‐2 outbreak is severely disturbing the worldwide economy at present. The urgent need of recent times is to understand the environmental aspect of COVID‐19 disease. Hence to fulfill this point, the present review article is compiled with a brief discussion about all the minute points of the COVID‐19 pandemic related to the environment: origin and present scenario, the occurrence of SARS‐CoV‐2 in environmental habitats, the effect of COVID‐19 on human health, and environment, environmental factors influencing the transmission and spreading of SARS‐CoV‐2. This review explains micro and macro pollutants in hospital and urban wastewater influencing COVID‐19, detection of SARS‐CoV‐2, current global drug strategies to control replication and spread of SARS‐CoV‐2 from the environment, future approaches, and guidelines to prevent and control upcoming pandemics. The SARS‐CoV‐2 structural details and their effect on humans have been already well presented but the research about environmental factors affecting COVID‐19 could be important points to fight present and future pandemics. Abstract : The impact of environmental pollutants on COVID‐19.